Determining and comparing the level of motivation for exercise according to the sociodemographic characteristics of university students - Mohammad Ahsan; Mohammed Feroz Ali; Mumtaz Alam (BMC Public Health)
Abstract Background Motivation levels for exercise vary widely among individuals and are influenced by various factors. This study aimed to compare exercise motivation levels and explore influencing factors among university students. Methods A cross-sectional research design targeted university students aged range 18 to 32 years. Participants (n = 148) were selected via cluster random sampling. Motivation for exercise was determine by the Exercise Motivation Inventory (EMI-2). EMI-2 comprises fourteen different subscales of motivation, with each subscale containing three to four items. All items were rated on a scale of 0 to 5, with 0 indicating “not at all true for me” and 5 indicating “very true for me.” Statistical analyses included ANOVA and Pearson correlation coefficient to assess differences among demographic variables (year of study, age, gender, marital status, location, and family size) and relationships between motivational aspects. Results The average exercise motivation level among all students was 166.94 ± 32.20. Fifth-year students exhibited the highest motivation 178.33 ± 30.37. No significant gender differences were found (p = 0.149). However, age (p = 0.024), location (p = 0.015), marital status (p = 0.050), and family size (p = 0.030) significantly influenced exercise motivation. Conclusion University students demonstrate inherent motivation for physical activity, with significant variations observed across demographic factors. These findings underscore the importance of tailored interventions to promote exercise and enhance student well-being. Further research, including longitudinal studies, is warranted to comprehensively understand exercise motivation dynamics in this population.